Satisfaction of older adults with Chile’s “meeting centres” social education programme - Araya Cuello, Marlene; Fernández Martínez, María del Mar; Hernández Garre, Carmen María; Carrión Martínez, José Juan (Cuadernos de Trabajo Social, 2020)
In Chile, “meeting centres” (Casas de encuentro) are attended by older adults during the daytime in order for them to participate in activities to encourage active ageing. They also offer programmes involving social education activities. This article examines older adults’ satisfaction with the training/education that they receive. The study has a descriptive and non-experimental design. The Valparaíso meeting centre was the context for the study, with 205 older adults participating. Data were obtained using an ad hoc questionnaire with a Likert-type scale. The main findings are as follows: high level of satisfaction among older adults, related not to their sociodemographic characteristics such as gender, educational level or previous occupation, but to their prior expectations. The general conclusion is that these programmes are a source of satisfaction among older adults, beyond the particular competencies that each programme might be intended to foster. They should be one of the key factors guiding social policy to encourage active ageing, which is emerging as an increasingly pressing need.